1998
DOI: 10.1023/a:1005458703363
|View full text |Cite
|
Sign up to set email alerts
|

From toxicological problem to therapeutic use: The discovery of the mode of action of 2‐(2‐nitro‐4‐trifluoromethylbenzoyl)‐1,3‐cyclohexanedione (NTBC), its toxicology and development as a drug

Abstract: NTBC is a triketone with herbicidal activity that has been shown to have a novel mode of action by inhibiting the enzyme 4-hydroxyphenylpyruvate dioxygenase in plants. Early studies on the toxicity of this compound found that rats treated with NTBC developed corneal lesions. Investigations aimed at understanding the mechanistic basis for the ocular toxicity discovered that the rats developed tyrosinaemia and excreted large amounts of 4-hydroxyphenylpyruvate and 4-hydroxyphenyllactate, owing to inhibition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…This pharmacologic intervention prevents the formation of maleyl- and fumarylacetoacetate as well as relevant derivatives all of which are known to cause the pathologies observed in TYR I [8]. Along with a phenylalanine and tyrosine reduced diet, oral NTBC has become the mainstay of treatment for TYR I patients.…”
Section: Introductionmentioning
confidence: 99%
“…This pharmacologic intervention prevents the formation of maleyl- and fumarylacetoacetate as well as relevant derivatives all of which are known to cause the pathologies observed in TYR I [8]. Along with a phenylalanine and tyrosine reduced diet, oral NTBC has become the mainstay of treatment for TYR I patients.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Because pre-clinical toxicological and pharmacokinetic data for 1 are mainly derived from comprehensive records based on different animal models, [12][13][14] human safety margins cannoty et be fully determined. [8][9][10][11] Because pre-clinical toxicological and pharmacokinetic data for 1 are mainly derived from comprehensive records based on different animal models, [12][13][14] human safety margins cannoty et be fully determined.…”
mentioning
confidence: 99%
“…In patients with hereditary tyrosinemia type 1, these catabolic intermediates are converted to the toxic metabolites succinylacetone and succinylacetoacetate, which are responsible for the observed liver and kidney toxicity. Nitisinone was originally discovered as an herbicide, but early mechanism-of-action studies in rats revealed that the compound caused a marked increase in plasma tyrosine concentrations [22]. …”
Section: Discussionmentioning
confidence: 99%